THE STRUGGLE OF THE MAIN CHARACTER IN THE MOVIE DJANGO UNCHAINED BY QUENTIN TARANTINO - Istiwarni Diah; Latifah Nuraini (Journal of English Language and Literature (JELL), 2018)
The purpose of this research is to find out how struggle of the main character against injustice from the white people around them. The research is conducted by using qualitative method; the writer uses two data sources, namely primary and secondary data source. The primary data is movie Django Unchained directed by Quentin Tarantino. The secondary data sources are the other sources related to this thesis like books about the movie. There are three objectives of this study. First, the kind of struggle of the main character as a slave that shows in movie. Second, factors that influenced black people become slave in movie. It makes black people get pressure from white people. Third the way slave can survive in pressure of white people. The results of the research are as follows; in the end, it can be concluded that the struggle for freedom can find happiness. Finally, Django as a main character and other slaves get their struggle for freedom after overcoming against their master.